Hubungan Kontrol Diri dan Pengalaman Mengikuti Konseling Kelompok terhadap Penerimaan Diri Siswa di Sekolah Menengah Pertama - Nunung Parwati; Dwi Yuwono Puji Sugiharto (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to determine the relationship of self-control, group counseling services, and self-acceptance of class VIII students of SMP Negeri 1 Ungaran. This research is a type of quantitative research with ex post facto research methods and correlational research design. The research subjects were 161 students from 314 students with a sampling technique that was random sampling. The instrument used in this study consisted of a self-control scale, a scale of experience following group counseling and a scale of self-acceptance. The validity test uses the product moment formula and the reliability test uses the alpha formula and to analyze the data using the data normality test, linearity test, product moment and multiple correlation. The results of the analysis show that the significant value of the relationship between self-control and the experience of participating in group counseling on self-acceptance is 0.000 <0.05 and the R-value is 0.532. So it can be concluded that there is a relationship between self-control and the experience of participating in group counseling on self-acceptance and is categorized as moderate